Sap Flow Responses to Warming and Fruit Load in Young Olive Trees - Miserere, Andrea; Searles, Peter S.; Manchó, Guadalupe; Maseda, Pablo H.; Rousseaux, Maria Cecilia (Frontiers in Plant Science, 2019)
Global warming will likely lead to temperature increases in many regions of South America where temperatures are already considered to be high for olive production. Thus, experimental studies are needed to assess how water use in olive trees may be affected by global warming. The objectives of this study were to: i) evaluate the response of olive tree sap flow, stomatal conductance, and xylem anatomy to elevated temperature; and ii) determine whether fruit load may affect the temperature responses. A warming experiment using well-irrigated olive trees (cv. Arbequina) in open top chambers (OTCs) with two temperature levels was performed from fruit set to the end of fruit growth in two seasons. Temperature levels were a near ambient control (T0) and a treatment 4 °C above the control (T+). Trees were either in the chambers for one (2015-16) or two seasons (2014-15, 2015-16) and were evaluated only in the second season when all trees were three years-old. Whole-tree sap flow on leaf area basis, stomatal conductance, and aspects of xylem anatomy were measured. Sap flow was slightly higher in T+ than T0 trees heated for one season early in fruit development (summer) likely due to the elevated temperature and increase in vapor pressure deficit. Later in fruit development (fall), sap flow was substantially higher in the T+ trees heated for one season. Total vessel number per shoot was greater in the T+ than the T0 trees at this time due to more small diameter vessels in the T+ trees, but this did not appear to explain the greater sap flow. The T+ trees that were heated for two seasons had less fruit load than the T0 trees due to little flowering. In contrast to trees heated for one season, sap flow was less in T+ than controls late in fruit development the second season, which was likely related to lower fruit load. An independent experiment using untreated trees confirmed that sap flow decreases when fruit load is below a threshold value. The results emphasize that multiple, interacting factors should be considered when predicting warming effects on water use in olive orchards.